KONTRIBUSI INFORMASI KARIR TERHADAP MINAT BERWIRAUSAHA SISWA JASA BOGA DI SEKOLAH MENENGAH KEJURUAN NEGERI 9 PADANG - Fresiskha, Jenny; Yulastri, Asmar; Chair, Ira Meirina (Journal of Home Economics and Tourism, 2013)
This study aims to (1) describe the career information Jasa Boga students SMKN Padang 9, (2) describe the Jasa Boga students interest in entrepreneurshipt SMKN Padang 9 and (3) reveal the contribution of career information to Jasa Boga students' interest in entrepreneurship in SMKN 9 Padang. This study is a descriptive correlational study. The study populationwas Jasa Boga student’sof class XIISMK 9Padangin the academic year2012/2013as many as102students. Samples were obtained from 50% of a population of 51 students. Collecting data using a structured questionnaire with Likert scale.Questionnaire used had been tested for validity and reliability. The descriptive analysis of the results showed that the students' career information categorized quite good (37%) and interest in entrepreneurship categorized quite good (45%). Correlation coefficient between the variables of career information with interest in entrepreneurship (r2) = 0.096 means career information contributed 9.6% to as much interest in entrepreneurship. While the rest (90.4%) affected other variables. The results showed that the students' career information obtained is still less than the maximum. Therefore need to be increased efforts to provide information about career. Therefore need to be increased efforts to provide information about careers. So that students will understand and have a career choice before completing school. Keywords: Career Information, Interests Entrepreneurship, SMK students